Work-life balance -a systematic review - Thilagavathy S.; Geetha S.N. (Vilakshan (XIMB Journal of Management))
Purpose – This study aims to systematically review the existing literature and develop an understanding of work-life balance (WLB) and its relationship with other forms of work-related behavior and unearth research gaps to recommend future research possibilities and priorities. Design/methodology/approach – The current study attempts to make a detailed survey of the research work done by the pioneers in the domain WLB and its related aspects. A total of 99 research work has been included in this systematic review. The research works have been classified based on the year of publication, geographical distribution, the methodology used and the sector. The various concepts and components that have made significant contributions, factors that influence WLB, importance and implications are discussed. Findings – The paper points to the research gaps and scope for future research in the area of WLB. Originality/value – The current study uncovered the research gaps regarding the systematic review and classifications based on demography, year of publication, the research method used and sector being studied.